Chitosan-Derived Magnetic Nanomaterials: Synthesis, Characterization, and Nitrite Adsorption in Water. (18th August 2021) - Liu, Tong; Fu, Jingyi; Gou, Dongxia; Hu, Yanbo; Tang, Qilong; Zhao, Jun; Li, Xiaohong
Abstract : Nitrite is one of the main pollutants in the water worldwide. In this study, we have applied the reverse suspension crosslinking methodology based on chitosan (CS) and Fe3 O4 (FeO) to synthesize the novel magnetic nanomaterial of chitosan (CS-FeO). The physical and chemical properties of CS-FeO were further characterized by scanning electron microscopy, particle size distribution, thermogravimetry, fluxgate magnetometer, Fourier transform infrared spectroscopy, X-ray diffraction spectroscopy, and energy dispersive spectroscopy. Results revealed that CS-FeO showed high thermal stability in the temperature ranging from 50 to 200°C. CS-FeO showed high crystallinity and magnetism and was easily and quickly separated from aqueous solution in the presence of an external magnetic field. The molecular structure of CS-FeO showed that the core-shell structure of CS-FeO was established with FeO as the core and CS as the shell. Furthermore, the adsorption rate of nitrite by CS-FeO reached 65.83 ± 0.76 % under optimal conditions. Moreover, CS-FeO showed high regeneration capability with Na2 SO4 used as the eluent. Our study demonstrated evidently that CS-FeO can be potentially used to remove nitrite from drinking water sources and industrial wastewater, suggesting the promising future of the application of CS-derived magnetic nanomaterials in the areas of environmental protections.